GERAKAN SISWA CERDAS FINANSIAL: PEMBERDAYAAN LITERASI KEUANGAN DASAR DI SD MUHAMMADIYAH BANYURADEN - Latifah Putranti; Pradita Nindya Aryandha; Anantika Putri Nur Khasanah; Wahyu Azizah Putri; Vanesa Dinda Tri Wulandari; Bagas Saputra (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
This community service activity was conducted to improve students’ basic financial literacy at Muhammadiyah Elementary School in Banyuraden, given the low understanding among elementary school-aged children of basic concepts in money management, saving habits, and responsible financial behavior. The “Financially Smart Student Movement” program was designed to empower financial literacy through an educational, participatory, and interactive approach that includes counseling methods, educational games, savings practices, and mentoring through simple learning modules. The goal of this activity was to foster a basic understanding of the value of money, needs and wants, and simple financial planning, and to develop savings habits from an early age. The implementation results showed an increase in students’ knowledge of basic financial concepts, changes in attitudes toward frugality and focus, and increased motivation to save regularly. Based on these results, it is recommended that schools integrate financial literacy into daily activities, strengthen collaboration with local financial institutions, and develop follow-up programs to deepen children’s understanding of financial matters.